Tripodalsporormielones A-C, unprecedented cage-like polyketides with complex polyvdent bridged and fused ring systems - Guodong Chen; Bingxin Zhao; Meijuan Huang; Jia Tang; Yanbing Li; Liangdong Guo; Rongrong He; Dan Hu; Xinsheng Yao; Hao Gao (Elsevier, 2021)
A chemical investigation on Sporormiella sp. led to the isolation and structural elucidation of tripodalsporormielones A-C (1-3), a new class of polyketide possessing unprecedented cage-like skeletons with polyvdent bridged and fused ring systems. These polyketides with cage-like skeletons were characterized as a high non-protonated carbon-containing system, which resulted in few HMBC correlations observed and made the accurate structures hard to be obtained by NMR. Especially, some signals of non-protonated sp2 carbons are weak and even unobservable in compound 1. In order to establish the structure of 1, the calculated NMR with DP4 evaluation was applied to determine the structure from the plausible structure candidates obtained from the detailed NMR analysis. Based on NMR experiments and calculated NMR, the structures of isolated compounds were established and confirmed by X-ray technology. Through chiral isolation, the optically pure enantiomers of 1 and 3 were obtained, and their absolute configurations were determined based on ECD quantum chemical calculation. Based on the isolated compounds and our previous work, 1-3 would be derived from 3-methylorcinaldehyde, and their plausible biosynthetic mechanism was proposed. Furthermore, 1 exhibited obvious short-term memory improvement activity on an Alzheimer's disease fly model.